Radiosensitisation of SCCVII tumours and normal tissues in mice by the DNA-dependent protein kinase inhibitor AZD7648. (January 2022) - Hong, Cho R.; Buckley, Chantal D.; Wong, Way W.; Anekal, Praju V.; Dickson, Benjamin D.; Bogle, Gib; Hicks, Kevin O.; Hay, Michael P.; Wilson, William R.
Graphical abstract: Highlights: DNA-PK inhibitor AZD7648 potently radiosensitises HNSCC cell lines in vitro. The magnitude of radiosensitisation is similar under oxic and anoxic conditions. AZD7648 diffuses rapidly through multicellular layer cultures. Oral AZD7648 radiosensitises SCCVII tumours in mice. AZD7648 also radiosensitises acutely responding normal tissues (oral and GI mucosa) Abstract: Background and purpose: Inhibitors of DNA-dependent protein kinase (DNA-PK) are effective radiation sensitisers in preclinical tumours, but little is known about risks of normal tissue radiosensitisation. Here, we evaluate radiosensitisation of head and neck squamous cell carcinoma (HNSCC) cells by DNA-PK inhibitor AZD7648 under oxia and anoxia in vitro, and tumour (SCCVII), oral mucosa and small intestine in mice. Materials and methods: Radiosensitisation of human (UT-SCC-54C) and murine (SCCVII) HNSCC cells by AZD7648 under oxia and anoxia was evaluated by clonogenic assay. Radiosensitisation of SCCVII tumours in C3H mice by oral AZD7648 (75 mg/kg) was determined by ex vivo clonogenic assay 3.5 days post-irradiation, with evaluation of normal tissue surrogate endpoints using 5-ethynyl-2′-deoxyuridine to facilitate detection of regenerating crypts in the ileum and repopulating S-phase cells in the ileum and oral mucosa of the same animals. Results: AZD7648 potently radiosensitised both cell lines, with similar sensitiser enhancement ratios for 10% survival (SER10 ) under oxia and anoxia. AZD7648 diffused rapidly through multicellular layers, suggesting rapid equilibration between plasma and hypoxic zones in tumours. SCCVII tumours were radiosensitised by AZD7648 (SER10 2.5). AZD7648 also enhanced radiation-induced body weight loss and suppressed regenerating intestinal crypts and repopulating S-phase cells in the ileum and tongue epithelium with SER values similar to SCCVII tumours. Conclusion: AZD7648 is a potent radiation sensitiser of both oxic and anoxic tumour cells, but also markedly radiosensitises stem cells in the small intestine and oral mucosa.